Serie E, Nr. 17010: Unbekannte Gesellschaft (Gesellschaft Für Deutsch-Deutsche Freundschaft) - Penck, A.R., (1989)
Serie E, Nr. 17010: Unbekannte Gesellschaft (Gesellschaft Für Deutsch-Deutsche Freundschaft).